A large-scale molecular model of Fenghuangshan anthracite coal. (1st July 2021) - Zhang, Yu; Hu, Sherong; Zhong, Qifan; Zhuo, Jiankun; Mathews, Jonathan P.
Highlights: A complex and largest scale anthracite coal representation (C115925 H42127 O892 N764 S919 ) constructed. Coal model captures, organization (stacking and degree of orientation), molecule curvature, heteroatom functionality, and much of the micropore size distribution. A wide variety of chemical and physical parameters were consistent with experimental data. Abstract: A large-scale (C115925 H42127 O892 N764 S919 ) atomistic representation of Fenghuangshan anthracite was constructed using an image-guided approach informed by high-resolution transmission electron (HRTEM) micrographs. Additional structural information was obtained from solid state 13 C NMR, XRD, laser desorption ionization mass spectra (LDIMS), XPS, and gas adsorption. The structure captures the crystalline characteristics, aromaticity, organization (stacking and degree of orientation), molecule curvature, heteroatom functionality, and much of the micropore size distribution. Construction used Fringe3D and Vol3D scripts to generate slice and volumetric representations with others added heteroatoms. Curvature in the aromatic components was generated manually by adjusting 5- and 7-membered rings frequency and placement. The micropore size distribution was included by incorporating additional pores to supplement the inherent porosity created between structural components. The use of flattened pores also demonstrated a measure of control over pore shapes and captured the coalification induced pore orientation within anthracite coal. Cross-linking is currently omitted however as the frequency and placement are unknown and an automated appropriate cross-linking approach while retaining orientation and stacking is not yet available.